A libertarian theory of property: its justification, critique and implications - Williams, Graham Andrew (Department of Philosophy, 2023)
The author's major concern in this dissertation is a justification, it's critique and some of its implications, of the libertarian theory of property according to which property, following John Locke, is legitimately acquired through a man's mixing of his labour with unowned resources and held in perpetuity or until the owner voluntarily alienates his just claim. Libertarian theory asserts that property thus acquired is held by natural right. Accordingly, this dissertation commences with an elucidation of how we are to understand the concept of property and the concept and language of natural rights. The dissertation then attempts to show that: .1. The concept of universal natural right, at least in relation to private property, is not non-sensical. 2. The libertarian justification of exclusive private property can be argued for coherently. 3. Universality in the natural right to private property entails (coercive) redistribution. Over 3 the author departs from the 'orthodox' libertarianism of Murray Rothbard, Ayn Rand and John Hospers in favour of a 'welfarist' libertarianism that is more in accord with the positions of Robert Nozick, Milton Friedman, Friedrich v. Hayek and others, and which is closer to the spirit of Locke's Second Treatise. Welfarist libertarianism leads the dissertation through 4. Marx's critique of private property and capitalist political economy. 5. Liberal/non-Marxist arguments advocating equality or greater egalitarianism. 6. Certain implications welfarist libertarianism holds regarding the justification, extent, and operations of the state. The conclusions the author arrives at include: 1. There is a natural right to limited exclusive private property. 2. Property is limited not in its acquisition but in its (perpetual) holding. 3. Redistribution may be coercive, but that coercion is legitimated on grounds of justice. 4. Property rights preserve the liberty of some but necessarily infringe the liberty of others. This too is legitimated on grounds of justice. 5. The Marxist argument that private property and capitalist political economy is exploitative is mistaken, and that it alienates man an argument insufficiently contended for. 6. Egalitarianism and greater egalitarianism as political policies are wrong if welfarist libertarianism is just. Bot? also fail to accord persons a sufficiently central place in moral-political philosophy. Egalitarianism is, furthermore, necessarily self-defeating. 7. The state is not necessary for the protection of our lives, liberty, and property nor for the implementation of redistribution. These functions could be performed through the free market. Should a state justly evolve from the market it cannot ensure its stability due to the pressures morally demanded financial obligations impose upon it.